2007
DOI: 10.4046/trd.2007.63.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sensitivity of Human Lung Cancer Cell Line to TRAIL and Gefitinib by IGF-1R Blockade

Abstract: Background: TRAIL is a cytokine that selectively induces apoptosis in various cancer cell lines. Gefitinib is new targeted drug applied in lung cancer that selectively inhibits EGFR tyrosine kinase. However, lung cancers have shown an initial or acquired resistance to these drugs. This study examined the effect of IGF-1R and its blockade on enhancing the sensitivity of lung cancer cell lines to TRAIL and gefitinib. Methods: Two lung cancer cell lines were used in this study. NCI H460 is very sensitive to TRAIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Many studies have shown that Akt directly phosphorylates FOXO transcription factors (37)(38)(39) and the mechanisms through which Akt regulates FOXO transcription factors have been previously elucidated (40). Phosphorylation of FOXO by Akt triggers the rapid relocalization of FOXO proteins from the nucleus to the cytoplasm and results in the inhibition of FOXO-dependent transcription of its target genes, such as FasL and Trail (41)(42)(43)(44)(45). Because FOXO is intimately associated with the death-receptor mediated apoptotic pathway, we investigated the possibility that the FOXO family proteins may act as mediators of the increased apoptosis observed in shPrx1-infected A549 cells treated with docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that Akt directly phosphorylates FOXO transcription factors (37)(38)(39) and the mechanisms through which Akt regulates FOXO transcription factors have been previously elucidated (40). Phosphorylation of FOXO by Akt triggers the rapid relocalization of FOXO proteins from the nucleus to the cytoplasm and results in the inhibition of FOXO-dependent transcription of its target genes, such as FasL and Trail (41)(42)(43)(44)(45). Because FOXO is intimately associated with the death-receptor mediated apoptotic pathway, we investigated the possibility that the FOXO family proteins may act as mediators of the increased apoptosis observed in shPrx1-infected A549 cells treated with docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that Akt directly phosphorylates FOXO transcription factors33,34, and the mechanisms through which Akt regulates FOXO transcription factors have been previously elucidated35. Phosphorylation of FOXO by Akt triggers rapid relocalization of FOXO proteins from the nucleus to the cytoplasm leading to inhibition of FOXO-dependent transcription of its target genes such as FasL and TRAIL26,36,37. We have found that A549 xenograft tumors express FOXO1, but not other members of the FOXO family (data not shown).…”
Section: Discussionmentioning
confidence: 99%